3D InGaN nanowire arrays on oblique pyramid-textured Si (311) for light trapping and solar water splitting enhancement. (May 2021) - Chen, Hedong; Wang, Peng; Wang, Xingyu; Wang, Xingfu; Rao, Lujia; Qian, Yinping; Yin, Hongjie; Hou, Xianhua; Ye, Huapeng; Zhou, Guofu; Nötzel, Richard
Abstract: We study Ⅲ-nitride nanowire (NW) anti-reflection structures employed as photoelectrocatalyst for solar water splitting. We found that 1D vertical InGaN NW arrays tilted by 73° exhibit maximized photocurrent. Therefore, we grow 3D InGaN NW arrays on the facets of oblique pyramid-textured Si (311) (OPSi/InGaN) by plasma-assisted molecular beam epitaxy, exhibiting facets tilted by 73°. In addition, using finite difference time domain simulations we find the crucial impact of the asymmetry of the oblique pyramid InGaN NW arrays on the light trapping. Compared with InGaN NWs grown on a planar Si substrate (Si/InGaN), the OPSi/InGaN photoanode exhibits ~500% enhancement of the photocurrent due to various light trapping effects attributed to: 1D vertical NW arrays, their tilt, 3D arrangement and asymmetry. Decorated with NiOOH co-catalyst, the OPSi/InGaN photoanode exhibits photocurrent densities in the mA cm −2 range. The present research provides a rational design for the fabrication of nanostructured photoelectrocatalyst with enhanced light absorption. Graphical Abstract: ga1 Highlights: 3D InGaN NW arrays are grown vertically on oblique pyramidal substrate. OPSi/InGaN possesses synergistic combination of light trapping effects. OPSi/InGaN exhibits ~500% enhancement in photocurrent than 1D InGaN NW arrays. InGaN NW arrays with 73° tilt angle on OPSi exhibit maximized photocurrent. Asymmetry of oblique pyramids enhances the light trapping.